Selected Safety Issues During The First Wave of The Coronavirus Pandemic at Elementary and Secondary Schools - Radim ŠTĚPÁNEK; Veronika ŠVRČINOVÁ; Svatopluk SLOVÁK; Pavel DOSTÁL (Communications of International Proceedings, 2021)
The first wave of the Covid-19 pandemic affected run-in motion of schools in the Czech Republic via the decree from the Department of Health. With the effect from 11 March 2020 the attendance of pupils was forbidden at basic and secondary schools and at colleges. From 11 May 2020 the situation was gradually releasing the students of final grades of secondary schools, conservatories and colleges could attend their lessons especially because of their preparation for school-leaving exams and final exams. Pupils of ninth grades of elementary schools could attend their lessons, too, because of their preparation for entrance examinations to secondary schools. Their attendance was not compulsory and the lessons were performed in groups of maximum 15 people. This article focuses on the analysis of the nation-wide survey in the area of keeping the selected safety issues at schools that realised intensively school lessons for groups of pupils mentioned above. The results of this nationwide research of opinions of teachers were acquired by a questionnaire method. There was a majority of structural items of polytomy character and scale rating of Likert type.
Keywords: Closing Of Schools; Distant Education; Safe Education In The Covid-19 Period; Keeping The Hygienic Instructions; Pedagogy; Students